Desain Ergonomis Kursi Kuliah Untuk Mahasiswa Kidal: Integrasi Analisis Antropometri dan Rapid Upper Limb Assesment - Yuselin, Nensi; Setiawan, Indra; Zahabiyah, Rifdah; Rosyidi, Edwar; Aisa, Neilinda Novita; Sidik, Pramana; Faizin, Deni Nur; Dewani, Thalita (Universitas Suryakancana, 2024)
Learning facilities such as chairs are learning tools that must be available to facilitate teaching activities. This can affect concentration and productivity in the learning process in the classroom. Astra Polytechnic is a private vocational college that implements a lecture time system of 8 hours per day. The length of the learning process is not supported by adequate facilities such as not having chairs specifically designed for left-handed students. In fact, the number of left-handed people reached 20 people in 2023 or 2.5% of the total students. Based on initial observations through sampling interviews with several left-handed students, this makes it difficult for students to write. In addition, the existing chairs do not match the dimensions of the students' body posture. The purpose of this study is to improve the ergonomic value of lecture chairs for left-handed students by considering the components and dimensions of the appropriate product. Improvements were made by creating an ergonomic chair design and making a prototype. After that, the process was evaluated using the Rapid Upper Limb Assessment (RULA) method. The results of the study were in the form of a prototype ergonomic design of a lecture chair for left-handed students with dimensions that had been adjusted by considering replacing the backrest and seat to be softer. The evaluation results show a value of 3 or are included in the